Sharing Lives Adult Children and Parents - Szydlik, Marc (Routledge Advances in Sociology, 2016)
Sharing Lives explores the most important human relationships which last for the longest period of our lives: those between adult children and their parents. Offering a new reference point for studies on the sociology of family, the book focuses on the reasons and results of lifelong intergenerational solidarity by looking at individuals, families and societies. This monograph combines theoretical reasoning with empirical research, based on the Survey of Health, Ageing and Retirement in Europe (SHARE). The book focuses on the following areas: ● Adult family generations, from young adulthood to the end of life, and beyond ● Contact, conflict, coresidence, money, time, inheritance ● Consequences of lifelong solidarity ● Family generations and the relationship of family and the welfare state ● Connections between family cohesion and social inequality. Sharing Lives offers reliable findings on the basis of state-of-the-art methods and the best available data, and presents these findings in an accessible manner. This book will appeal to researchers, policymakers and graduate students in the areas of sociology, political science, psychology and economics.